Transformation in Postmigrant Societies: Contextualizing Jochen Oltmer’s Concept of Negotiation (Zeitschrift für Migrationsforschung, 2025)
Drawing on diverse theoretical and perspectival approaches, such as »superdiversity«, »transnationality«, and »autonomy of migration«, this article situates Oltmer’s concept of »negotiation« in current debates in migration research and examines how it can be linked to the perspective of the »postmigrant«. While the latter assumes that the distinction between migrants and non-migrants is becoming increasingly irrelevant for a productive analysis of social contexts, this remains valid for the present time with regard to negotiations. Simultaneously, the focus on negotiations enables analytical clarity and historical depth, which contribute to an understanding of the change in the social concepts of belonging.Transformation in postmigrantischen Gesellschaften: Zur Einordnung von Jochen Oltmers Konzept der AushandlungAusgehend von einer Vielzahl theoretischer und perspektivischer Zugänge der Migrationsforschung wie »Superdiversität«, »Transnationalität« oder »Autonomie der Migration« verortet der Beitrag Oltmers Konzept der »Aushandlung« in aktuellen Debatten der Migrationsforschung und fragt, inwiefern er mit der Perspektive des »Postmigrantischen« in Verbindung zu bringen ist. Während Letztere davon ausgeht, dass die Unterscheidung von Migrant:innen und Nicht-Migrant:innen für eine produktive Analyse sozialer Zusammenhänge zunehmend bedeutungslos wird, bleibt die Zuschreibung im Blick auf Aushandlungen zunächst bestehen. Zugleich ermöglicht der Fokus auf die Aushandlungen analytische Klarheit und historische Tiefe, die zum Verständnis des Wandels gesellschaftlicher Vorstellungen von Zugehörigkeit beitragen.
Keywords: Migrationsforschung; Aushandlung; Postmigrantisches Paradigma; Migrationsregime